Emotion recognition in autism spectrum condition during the COVID-19 pandemic - Schnitzler, Tim; Korn, Christoph W.; Herpertz, Sabine; Fuchs, Thomas (Autism, 2024)
With the widespread use of masks in the COVID-19 pandemic, it is crucial to understand how emotion recognition is affected by partial face covering. Since individuals with autism spectrum condition often tend to look at the lower half of the face, they are likely to be particularly restricted in emotion recognition by people wearing masks, since they are now forced to look at the upper half of the face. This study compared the recognition of basic and complex emotions in individuals with and without autism spectrum condition, when faces were presented uncovered, with face masks, or with sunglasses. We also used eye tracking to examine group differences in gaze patterns during emotion recognition. Individuals with autism spectrum condition were less accurate at recognizing emotions in all three conditions. Averaged across the three stimulus types, individuals with autism spectrum condition had greater difficulty recognizing anger, fear, pride, and embarrassment than control group. There was no group difference in emotion recognition between the three conditions. However, compared to individuals without autism spectrum condition, there was no evidence of either gaze avoidance or preference for the mouth region. Our results suggest that emotion recognition is reduced in individuals with autism spectrum condition, but this is not due to differences in gaze patterns. - Lay Abstract - In the COVID-19 pandemic, wearing face masks became mandatory to prevent the spread of the virus. However, they restrict the ability to recognize emotions to the upper part of the face. Since individuals with autism spectrum condition often tend to look at the lower half of the face, they may be particularly restricted in emotion recognition by people wearing masks, since they are now forced to look at the upper half of the face. The current study compared the recognition of facially expressed emotions between individuals with and without autism spectrum condition. Each photo was shown in three types, once uncovered, once with face mask, and once with sunglasses. Our results revealed a reduction in accuracy of individuals with autism spectrum condition at recognizing emotions in all three stimulus types and exhibited more difficulties distinguishing anger, fear, pride, and embarrassment. During the emotion recognition task, there was no difference in which facial areas the groups looked at. We did not find evidence that the disadvantages of individuals with autism spectrum condition in emotion recognition were due to looking at different areas of the face.